Analisis Persepsi Masyarakat Tergusur terhadap Dampak Sosial Ekonomi Program Citarum Harum - Khofifah, Winda; Waluya, Bagja; Abdullah, Mirna Nur Alia (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
The government is running the Citarum Harum program as an effort to restore the cleanliness of the Citarum River. The form of effort taken is by controlling buildings that do not have permits around the river. Binong sub-district, which contains the Cikapundung Kolot River and is a tributary of the Citarum River, was affected. This research aims to analyze the impact of the Citarum Harum Program on the socio-economic conditions of communities affected by evictions in Binong Village. The research method used is qualitative analysis by collecting data through interviews, observation and literature study. The research results show that the Citarum Harum Program has a significant impact on the socio-economic conditions of the affected communities. Economically, evictions cause a decrease in community expenditure due to the additional costs that must be incurred. Socially, evictions can disrupt the social stability of society, causing uncertainty, isolation and changes in social relationships.